Factors associated with oxidative stress and cancer risk in the Breast and Prostate Cancer Cohort Consortium. (March 2014) - Blein, S.; Berndt, S.; Joshi, A. D.; Campa, D.; Ziegler, R. G.; Riboli, E.; Cox, D. G.; ,; Gaudet, M. M.; Stevens, V. L.; Diver, W. R.; Gapstur, S. M.; et al.
Abstract Both endogenous factors (genomic variations) and exogenous factors (environmental exposures, lifestyle) impact the balance of reactive oxygen species (ROS). Variants of the ND3 (rs2853826; G10398A) gene of the mitochondrial genome, manganese superoxide dismutase (MnSOD; rs4880 Val16Ala) and glutathione peroxidase (GPX-1; rs1050450 Pro198Leu), are purported to have functional effects on regulation of ROS balance. In this study, we examined associations of breast and prostate cancer risks and survival with these variants, and interactions between rs4880–rs1050450, and alcohol consumption—rs2853826. Nested case-control studies were conducted in the Breast and Prostate Cancer Cohort Consortium (BPC3), consisting of nine cohorts. The analyses included over 10726 post-menopausal breast and 7532 prostate cancer cases with matched controls. Logistic regression models were used to evaluate associations with risk, and proportional hazard models were used for survival outcomes. We did not observe significant interactions between polymorphisms in MnSOD and GPX-1, or between mitochondrial polymorphisms and alcohol intake and risk of either breast (p-interaction of 0.34 and 0.98, respectively) or prostate cancer (p-interaction of 0.49 and 0.50, respectively). We observed a weak inverse association between prostate cancer risk and GPX-1 Leu198Leu carriers (OR 0.87, 95% CI 0.79–0.97, p = 0.01). Overall survival among women with breast cancer was inversely associated with G10398 carriers who consumed alcohol (HR 0.66 95% CI 0.49–0.88). Given the high power in our study, it is unlikely that interactions tested have more than moderate effects on breast or prostate cancer risk. Observed associations need both further epidemiological and biological confirmation.